2012
DOI: 10.1024/0301-1526/a000220
|View full text |Cite
|
Sign up to set email alerts
|

Carotid artery intima-media thickness and brachial artery flow-mediated vasodilatation in patients with rheumatoid arthritis

Abstract: In patients with RA, FMD was impaired and IMT was increased, indicating early endothelial dysfunction and accelerated atherosclerosis. Early treatment of disease may reduce the risk of atherosclerosis in RA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 21 publications
6
13
0
Order By: Relevance
“…In our study, the RA patients’ CIMT scores were significantly elevated. Similarly, Veselinovic et al determined that their RA patients’ CIMT scores were significantly higher than in the controls, and the brachial artery flow-mediated vasodilatation values were lower, which was attributed to the development of endothelial dysfunction and accelerated atherosclerosis13 ) . Adhikari et al also studied early RA patients, and they reported the same findings as previous researchers12 ) .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In our study, the RA patients’ CIMT scores were significantly elevated. Similarly, Veselinovic et al determined that their RA patients’ CIMT scores were significantly higher than in the controls, and the brachial artery flow-mediated vasodilatation values were lower, which was attributed to the development of endothelial dysfunction and accelerated atherosclerosis13 ) . Adhikari et al also studied early RA patients, and they reported the same findings as previous researchers12 ) .…”
Section: Discussionmentioning
confidence: 96%
“…In addition to predicting the presence of local atheroma, the findings of CIMT can reveal possible damage to the arterial system11 ) . Recent studies have shown increased CIMT scores in RA patients in contrast to healthy controls12, 13 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Other observational studies have demonstrated an association between corticosteroid use and lower rates of subclinical atherosclerosis compared to patients not using steroids [133]. Veselinovic and colleagues demonstrated that FMD is higher in RA patients treated with corticosteroids versus no therapy [124]. This study conflicts with a randomized prospective study, by Hafstrom, showing that addition of steroids to DMARD therapy does not improve endothelial function in RA patients [125].…”
Section: Effects Of Pharmacologic Interventions On Endothelial Funmentioning
confidence: 99%
“…The use of statins as disease modifying agents and as primary prevention for CVD in patients with chronic inflammatory diseases has also received interest. Statin therapy has been shown to reduce disease severity in patients with RA and has gained attention for use as a disease-modifying agent in other inflammatory diseases [124,125,133,134,135]. Statins have been also been shown to improve endothelium-dependent vasodilation in patients with RA and SLE [126,134,136,137].…”
Section: Effects Of Pharmacologic Interventions On Endothelial Funmentioning
confidence: 99%
“…+ DMARD30 daysCompared to baselineFMD5.0 % ± 1.9 vs 4.3 % ± 1.6 (NS)9Foster et al [47]England310.7-Methylprednisolone 500 mg (i.v. )Single doseCompared to baselineFMD3.3 % vs 3.1 % (NS)4Veselinovic et al [48]Serbia525.723.69 ± 0.84Prednisolone 7.5 mg/day (p.o.) + DMARDAt least 1 yearRA patients without GCFMD9.16 % ± 7.03 vs 12.6 % ± 5.49 P  = 0.0057Radhakutty et al [49]Australia18--Prednisolone 6 mg/day (p.o.…”
Section: Effects Of Gc On Endothelial Function In Ramentioning
confidence: 99%